Online Petition as a Type of Persuasive Discourse - Ghaltakhchyan, Siranoush (Armenian Folia Anglistika, 2013)
The article investigates the realization of the persuasive aim in online petitions with due regard to their linguistic and extra-linguistic features. Online petition is viewed as a modern form of persuasive discourse, which, however, has preserved the three important constituents of persuasion suggested by Aristotle – ethos, which refers to the impact by the authority of the speaker/listener; pathos which refers to the emotional impact achieved through linguistic and extra-linguistic means and logos that refers to the impact on the speaker’s consciousness through facts. The article highlights the linguistic means through which these constituents are expressed in electronic petitions, as well as the extent extra-linguistic factors may contribute to the successful realization of the persuasive impact.